2017
DOI: 10.1186/s12978-017-0351-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the support of pricking (female genital cutting type IV) among Somali immigrants – a cross-sectional study in Sweden

Abstract: BackgroundPricking, classified as female genital cutting (FGC) type IV by the World Health Organization, is an under-researched area gaining momentum among diaspora communities. Our aim was to explore factors associated with being supportive of pricking among Somalis in Sweden.MethodsIn a cross-sectional design, attitudes and knowledge regarding FGC, and measures of socioeconomic status, acculturation, and social capital, were assessed by a 49-item questionnaire in four municipalities in Sweden. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 30 publications
4
38
0
Order By: Relevance
“…All types of FGM/C are seen as violations of children's rights and are thus not allowed [16]. We agree with WHO [3] about FGM/C.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…All types of FGM/C are seen as violations of children's rights and are thus not allowed [16]. We agree with WHO [3] about FGM/C.…”
Section: Discussionsupporting
confidence: 75%
“…But, in the studies by Wahlberg et al [16] and by Refaat [17], it was observed to have an important religious aspect by men and women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the study was not designed to establish causality, it appears the shift from the pharaonic to the Sunna form of FGM/C is linked to health and well-being issues, specifically attempts to at least minimise any adverse impact upon them. In their study of FGM/C attitudes and knowledge among 648 Somali male and female immigrants in Sweden, Wahlberg et al (2017) reported 113 (17.4%) supported the continuation of pricking, with these more likely to believe it was acceptable religiously, not a violation of children's rights, and does not cause long-term health complications. Moreover, in 1985 Gallo, reporting positive attitudes to FGM/C among respondents, concluded such positivity partly found support in the ignorance of the negative aspects of the practice; given the often-delayed detrimental impact of the cutting years after its occurrence, not all women acknowledged the connection between cause and effect.…”
Section: Discussionmentioning
confidence: 99%